Academic lectures in an EFL context: An exploration of student and lecturer perceptions - Bashtovaya, Tatyana (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: The university teaching context is extremely broad and complex. However, among all the instructional methods available, lecturing is still the most used one in the 21st century. Given that lecturing is predominant in higher education, it is of vital importance to investigate what really goes on in those contexts from a pedagogical point of view. Owing to the scarcity of the research into lecture comprehension in a context where the language of lecture is English as a foreign language, the purpose of the present study is primarily to explore the perceived problems and difficulties of non-native English-speaking students in comprehending their course lectures, along with the possible sources of these difficulties. In addition, this study aims at investigating the ways that teachers organize lectures for their students in their classes. The study, then, addresses the following research questions: (1) What are the difficulties and their related sources in comprehending freshman year course lectures delivered in English from the perspective of (a) non-native English speaking students? (b) their course lecturers? (2) How do course lecturers pedagogically organize their lectures? (3) What kind of techniques assist better lecture comprehension according to (a) the students? (b) the course lecturers? This is a case study which is qualitative in nature, employing observation and audio recording of lectures, student questionnaires, and semi-structured lecturer-and-student interviews, based on actual lectures delivered in social science disciplines, namely Psychology, Business Administration, and International Relations. The study involved 149 students and seven lecturers from the above-mentioned departments. The findings of the current study point to the differences between the students’ and lecturers’ perceptions of the sources of difficulties and related problems in students’ comprehension of the content lectures in English. Further, the analysis of the audio-recorded and transcribed content lectures reveals that the participating lecturers differed in their lecturing styles and lecture organization, but were mostly similar in the ways of using discourse markers and visual aids. Furthermore, the research also displays that the techniques reportedly used by the lecturers to ensure lecture comprehension differ from those preferred by the students. In conclusion, this study provides some implications for more effective pedagogy in lecture comprehension in EFL contexts, as well as suggestions for prospective research. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Oldukça geniş ve karmaşık bir eğitim ortamına sahip olan üniversitelerde kullanılan pek çok öğretim metodunun varlığına karşın, 21. yüzyılda hala en fazla kullanılan yöntem, konferans biçiminde yapılan derslerdir. Bu nedenle, bu tür derslerin üniversite sınıflarında metod açısından nasıl yürütüldüğüne ilişkin araştırmalar büyük önem arzetmektedir. İngilizce’nin yabancı bir dil olarak kullanıldığı üniversite ortamlarında konferans derslerine ilişkin yapılmış çalışmaların azlığı göz önünde bulundurulduğunda, bu çalışma anadili İngilizce olmayan öğrencilerin üniversitedeki bölüm derslerini anlamalarında yaşadıkları sorunları ve bu sorunların olası nedenlerini araştırmayı hedeflemektedir. Buna ek olarak, bu çalışma öğretim görevlilerinin derslerini pedagojik açıdan nasıl düzenledikleri konusunu da incelemeyi amaçlamaktadır. Özetle, çalışmada şu araştırma sorularının yanıtları aranmaktadır: (1) Anadili İngilizce olmayan üniversite öğrencilerinin bölümlerindeki birinci sınıf derslerini anlamakta yaşadıkları zorluklar ve bu zorlukların nedenleri (a) öğrenciler açısından nelerdir? (b) öğretim görevlileri açısından nelerdir? (2) Öğretim görevlileri derslerini pedagojik açıdan nasıl düzenlemektedirler? (3) Dersi daha iyi anlamaya yardımcı olacak olan teknikler (a) öğrencilere göre nelerdir ? (b) öğretim görevlilerine göre nelerdir? Bu çalışma niteliksel bir durum araştırması olup, veri çalışmanın yapıldığı üniversitedeki Psikoloji, İşletme ve Uluslararası İlişkiler bölümlerinin 1. sınıflarında uygulanan gözlem, derslerin ses kayıtları, öğrencilere uygulanan anketler ile, öğretim görevlileriyle ve öğrencilerle yapılan mülakatlardan elde edilmiştir. Bu çalışmaya 149 öğrenci ile yukarıda belirtilen bölümlerden yedi öğretim görevlisi katılmıştır. Çalışmadan elde edilen sonuçlar, öğrencilerin İngilizce anlatılan dersleri anlamasını zorlaştıran sorunların kaynağı konusunda, öğrenciler ve öğretim görevlileri arasında fikir ayrılıklarının varlığını ortaya koymuştur. Buna ek olarak, sınıf-içi gözlemlerden ve derslerin ses kayıtlarından elde edilen bulgulara göre, çalışmaya katılan öğretim görevlilerinin her birinin derslerini düzenlemede ve sınıfta uygulamada farklı biçim ve yöntemlere sahip oldukları; bununla birlikte bağlaç ve görsel araç kullanımında benzer oldukları gözlemlenmiştir. Çalışmada ayrıca, konferans biçiminde sunulan derslerin daha iyi anlaşılmasına yardımcı olacak teknikler konusunda da, öğrencilerin ve öğretim görevlilerinin farklı düşündükleri ortaya çıkmıştır. Sonuç olarak, bu araştırma İngilizce’nin yabancı dil olarak kullanıldığı ders ortamları için verimli olabilecek eğitsel öneriler ve bu alanda yapılacak araştırmalara ışık tutacak öneriler sunmaktadır.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2013. Supervisor: Prof. Dr. Ülker Vancı Osam.
Keywords: Lecture method in teaching; Lectures and lecturing; English language - Foreign speakers; English for Academic Purpose (EAP) Academic Lectures Listening Comprehension in L2